Reconstruction and evolution analysis of long-term terrestrial water storage anomalies in Xinjiang based on time series decomposition and multi-model coupling - Zilong Li; Zhenxia Mu; Jing Liu; Xiaoyan Qiu (Journal of Hydrology, 2026)

Hydrogeomorphic controls of mouth bar on hyporheic exchange: Insights from experiments and numerical simulations - Jingsheng Jiang; Zhenxia Mu; Guangqiu Jin; Tuo Wang; Haiyu Yuan; Qihao Jiang; Hexiang Chen; Siyi Zhang (Advances in Water Resources, 2026)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Identification and three-dimensional evolution characterization of long duration and high severity drought in Xinjiang based on precipitable water vapor - Shikang Zhao; Zhenxia Mu; Zilong Li; Rongqin Yang; Mianting Huang (Atmospheric Research, 2025)

An Investigation Into the Long‐Chain Propagation Patterns and Driving Factors of Multiple Types of Droughts in Xinjiang - Shikang Zhao; Zhenxia Mu; Zilong Li; Xiaoyan Qiu; Jing Liu (International Journal of Climatology, 2025)
The process of drought propagation is extremely complex and involves all aspects of the water cycle. Clarifying the mechanism of drought propagation is of great significance for understanding the evolutionary pattern of drought and constructing a drought early warning system. However, due to the complexity of droughts and the numerous factors influencing them, there are certain limitations and shortcomings in studying the intrinsic links, propagation characteristics and triggering mechanisms of multiple drought types. To this end, this paper takes the Xinjiang region as the research object, identifies the drought events based on the run theory and determines the drought propagation time by matching the drought events; risk probabilities, trigger thresholds and drivers between different drought types were explored using copula functions, Bayesian theory and random forest models. The results show that (1) the average drought propagation time from meteorology to agriculture and from meteorology to hydrology in Xinjiang is 2.1 and 2.8 months, respectively. (2) The probability of the occurrence of agricultural (hydrological) drought increased with the severity of meteorological (agricultural) droughts. Specifically, the average probability of extreme meteorological (agricultural) droughts triggering mild agricultural (hydrological) droughts reached 89% (41%), with an average trigger threshold of −1 (−2.2). (3) Mild meteorological drought on the northern slopes of the Tianshan mountains was the primary trigger for mild agricultural drought, with an average trigger probability and threshold of 45% and −0.89, respectively. In contrast, moderate meteorological drought on the southern slopes of the Tianshan mountains was the main trigger for mild agricultural drought, with an average trigger probability and threshold of 56% and −1.1, respectively. (4) Meteorological drought triggers a significant reduction in the threshold for agricultural drought, mainly influenced by precipitation and potential evapotranspiration. Agricultural drought triggers a significant reduction in the threshold for hydrological drought, with temperature and potential evapotranspiration being the main drivers of the threshold change.

Relative humidity and solar radiation exacerbate snow drought risk in the headstreams of the Tarim River - Zhixia Wang; Shengzhi Huang; Zhenxia Mu; Guoyong Leng; Weili Duan; Hongbo Ling; Jia Xu; Xudong Zheng; Pei Li; Ziyan Li; Wenwen Guo; Yifei Li; et al. (Atmospheric Research, 2024)

Drought trigger thresholds for different levels of vegetation loss in China and their dynamics - Wenwen Guo; Shengzhi Huang; Qiang Huang; Guoyong Leng; Zhenxia Mu; Zhiming Han; Xiaoting Wei; Dunxian She; Hanye Wang; Zhixia Wang; Jian Peng (Agricultural and Forest Meteorology, 2023)

Construction of novel Heat-conducting Cu-based MOF nanocomposite (HK-mBNNS/PVDF) film for highly efficient Ad-/desorption of toluene - Junjie Li; Liming Liu; Syed Jalil Shah; Ying Tang; Shanliang Jiang; Guangyuan Mu; Quanru Man; Zhongxing Zhao; Zhenxia Zhao (Chemical Engineering Journal, 2023)